The Effectiveness of Breaststroke Training Using Slow Motion Video on Improving Basic Techniques of Physical Education Students at Pamulang University: The Effectiveness of Breaststroke Training Using Slow Motion Video on Improving Basic Techniques of Physical Education Students at Pamulang University - Wendri Maryadi; Acep Rohmat Nurhidayat; Ilona Pratiwi Hutabarat (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Abstract This study aims to examine the effectiveness of breaststroke swimming technique training using slow-motion video in improving the basic techniques of students in the Physical Education Program at Pamulang University. The research method employed was a quasi-experimental design with a pretest-posttest control group. The sample consisted of 40 students, divided into two groups: the experimental group received treatment using slow-motion video, while the control group underwent training using conventional demonstration methods. Assessment was conducted on five aspects of breaststroke technique: body position, arm movement, leg movement, breathing coordination, and movement rhythm.The results showed a significant improvement in technique scores in both groups, with the experimental group achieving a statistically higher improvement (p < 0.05). The average posttest score for the experimental group reached 20.15, while the control group only reached 16.85. The most notable improvements occurred in movement coordination and rhythm. The use of slow-motion video provided detailed visual feedback, allowing students to observe and correct movement errors independently. It can be concluded that slow-motion video is an effective learning medium for enhancing mastery of basic breaststroke techniques. These findings support the application of visual technology as an innovative strategy in motor skill learning, particularly in higher education physical education settings.